Effect of renal impairment on the pharmacokinetics and safety of dorzagliatin, a novel dual‐acting glucokinase activator - Jia Miao; Ping Fu; Shuang Ren; Chao Hu; Ying Wang; Chengfeng Jiao; Ping Li; Yu zhao; Cui Tang; Yuli Qian; Rong Yang; Yanli Dong; et al. (Wiley, 2022)
Abstract Dorzagliatin is a novel allosteric glucokinase activator targeting both pancreatic and hepatic glucokinase currently under clinical investigation for treatment of type 2 diabetes (T2D). This study aimed to investigate the effect of renal impairment (RI) on dorzagliatin's pharmacokinetics (PKs) and safety, and to guide appropriate clinical dosing in patients with diabetic kidney disease, including end‐stage renal disease (ESRD). Based on the results from physiologically‐based pharmacokinetic modeling, the predicted outcome of RI on dorzagliatin PK property would be minimum that the plasma exposure area under concentration (AUC) of dorzagliatin in patients with ESRD would increase at about 30% with minimal change in peak concentration (Cmax) comparing to those in healthy volunteers (HVs). To definitively confirm the prediction, a two‐part RI study was designed and conducted based on regulatory guidance starting with the patients with ESRD matched with HVs. Results of the RI study showed minimum difference between patients with ESRD and HVs with respect to dorzagliatin exposure with geometric mean ratio of ESRD to HV at 0.81 for Cmax and 1.11 for AUC. The elimination half‐life, volume of distribution, and systemic clearance for dorzagliatin were similar between the two groups. Dorzagliatin was well‐tolerated in patients with ESRD during the study. Therefore, RI showed no significant impact on dorzagliatin PK, suggesting that dorzagliatin can be readily used in patients with T2D at all stages of RI without need for dose adjustment.